Factors associated with purchasing pesticide from shops for intentional self‐poisoning in Sri Lanka. Issue 10 (5th August 2020) - Weerasinghe, Manjula; Konradsen, Flemming; Eddleston, Michael; Pearson, Melissa; Jayamanne, Shaluka; Knipe, Duleeka; Hawton, Keith; Gunnell, David; Agampodi, Suneth
Abstract: Objective: In South Asia, up to one in five individuals who ingest pesticides for self‐poisoning and survive purchased them from a shop immediately prior to the event. Thus far, no research has taken place to determine whether interventions implemented through the pesticide sellers might be acceptable or effective, despite the hundreds of thousands of such risk purchases each year. We aimed to investigate factors associated with purchasing pesticides for self‐poisoning in Sri Lanka. Methods: We used a case–control study. Cases ( n = 50) were individuals who ingested pesticides after purchasing them for the act, and controls ( n = 200) were customers who bought pesticides but did not use them for self‐harm. Logistic regression analysis was used to assess socio‐demographic and purchase‐specific risk factors. Results: Alcohol intoxication (adjusted odds ratios [AOR] 36.5, 95% confidence intervals [CI] 1.7–783.4) and being a non‐farmer AOR 13.3, 95% CI 1.8–99.6 were the main distinguishing factors when purchasing pesticides for self‐poisoning. The positive predictive values were 93.3% (95% CI 68.0–99.8%) and 88.2% (95% CI 72.5–96.7%), respectively. One and/or other of these factors characterised 72.0% of cases but only 2.5% controls. Conclusion: While results need to be interpreted cautiously, sales restrictions to prevent alcohol‐intoxicated persons and non‐farmers purchasing pesticides for self‐poisoning may be effective. Abstract : Objectif: En Asie du Sud, jusqu'à une personne sur cinq qui ingère des pesticides pour s'auto‐intoxiquer et survi les a achetés dans un magasin immédiatement avant l'événement. Jusqu'à présent, aucune recherche n'a eu lieu pour déterminer si les interventions mises en œuvre chez les vendeurs de pesticides pourraient être acceptables ou efficaces, malgré les centaines de milliers d'achats à risque chaque année. Nous visions à étudier les facteurs associés à l'achat de pesticides pour l'auto‐intoxication au Sri Lanka. Méthodes: Nous avons utilisé une étude cas‐témoins. Les cas (n = 50) étaient des personnes qui avaient ingéré des pesticides après les avoir achetés pour l'acte et les témoins (n = 200) étaient des clients qui achetaient des pesticides mais ne les utilisaient pas pour se faire du mal. Une analyse de régression logistique a été utilisée pour évaluer les facteurs de risque sociodémographiques et spécifiques à l'achat. Résultats: L'intoxication alcoolique (rapport de cotes ajusté [AOR] 36, 5, intervalles de confiance à 95% [IC] 1, 7‐783, 4) et étant un non‐agriculteur AOR 13, 3 ; IC95%: 1, 8‐99, 6 étaient les principaux facteurs distinctifs lors de l'achat de pesticides pour l'auto‐intoxication. Les valeurs prédictives positives étaient respectivement de 93, 3% (IC95%: 68, 0% ‐99, 8%) et 88, 2% (IC95%: 72, 5% ‐96, 7%). L'un et/ou l'autre de ces facteurs caractérisaient 72, 0% des cas mais seulement 2, 5% des témoins. Conclusion: Bien que les résultats doivent être interprétés avec prudence, des restrictions de vente visant à empêcher les personnes intoxiquées à l'alcool et les non‐agriculteurs d'acheter des pesticides pour l'auto‐intoxication peuvent être efficaces.